(untitled) (World Bulletin of Public Health, 2024)
Postpartum hemorrhage (PPH) is one of the serious complications that occurs in women after childbirth. PPH is defined as excessive bleeding of more than 500 ml after vaginal delivery or more than 1000 ml after cesarean section. PPH is one of the leading causes of maternal mortality worldwide and is thought to be caused by a combination of genetic and environmental factors [1]. This article provides information about genes leading to postpartum hemorrhage